Larval growth of Liosarcophaga Dux Thompson (Diptera : Sarcophagidae) under uncontrolled indoor temperatures in Malaysia - Kumara Thevan Krishnan (2013)
The larval growth of Liosarcophaga dux Thompson (Diptera: Sarcophagidae) was studied under varying indoor room temperatures in Malaysia. Five replicates were established. The immature growth of this species from first instar until adult emergence was 307.0±3.0 hours. The mean larval length measured for second instar, third instar, post-feeding stage and puparia were 6.5±0.5 mm (n=10), 11.8±3.7 mm (n=31), 12.7±0.8 mm (n=16), and 9.5±0.5 mm (n=15), respectively.